Odpowiedzi

2009-12-10T21:47:47+01:00
3(x-y)+4x=8
3(x-5y)=5-9y

3x - 3y + 4x =8
3x -5y = 5-9y

7x-3y=8//x4
3x+4y=5//x3

28x-12y=32
9x+12y=15

37x=47//:37
x=1 ¹⁰/₄₇

7x-3y=8//x(-3)
3x+4y=5//x7

-21x+9y=24
21x+28y=35

37y=59//:37
y=1 ²²/₃₇

x=1 ¹⁰/₄₇
y=1 ²²/₃₇
2009-12-10T21:53:53+01:00
3(x-y)+4x=8
3(x-5y)=5-9y

Obliczamy z pierwszego x
3x-3y+4x=8 -> 7x=3y+8/:7 x=3/7y+ 8/7
3x-15y=5-9y
3(3/7y+8/7)-6y=5
9/7y+24/7-6y=5
9/7y-42/7y=35/7-24/7
-33/7y=11/7 /×(-7/33)
y=-77/231=-11/33
x=3/7×(-11/33)+8/7=
-33/231+264/231=231/231=1